2009
DOI: 10.1007/s00253-008-1751-4
|View full text |Cite
|
Sign up to set email alerts
|

Direct production of cadaverine from soluble starch using Corynebacterium glutamicum coexpressing α-amylase and lysine decarboxylase

Abstract: Here, we demonstrated the one-step production of cadaverine from starch using a Corynebacterium glutamicum strain coexpressing Streptococcus bovis 148 alpha-amylase (AmyA) and Escherichia coli K-12 lysine decarboxylase (CadA). We constructed the E. coli-C. glutamicum shuttle vector, which produces CadA under the control of the high constitutive expression (HCE) promoter, and transformed this vector into C. glutamicum CSS secreting AmyA. The engineered C. glutamicum expressed both CadA and AmyA, which retained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
66
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(67 citation statements)
references
References 27 publications
0
66
0
1
Order By: Relevance
“…The organism is mainly used for the industrial production of amino acids, such as L-glutamate, L-lysine, or L-valine (28,52). Recent studies also showed the successful use of C. glutamicum for the production of organic acids (D-lactate, succinate), ethanol (24,36,37), xylitol (44), pantothenate (23), cadaverin (33,54), putrescine (45), and polyhydroxybutyrate (25). However, the targeted production of 2-ketoisovalerate with C. glutamicum has thus far not been reported.…”
mentioning
confidence: 99%
“…The organism is mainly used for the industrial production of amino acids, such as L-glutamate, L-lysine, or L-valine (28,52). Recent studies also showed the successful use of C. glutamicum for the production of organic acids (D-lactate, succinate), ethanol (24,36,37), xylitol (44), pantothenate (23), cadaverin (33,54), putrescine (45), and polyhydroxybutyrate (25). However, the targeted production of 2-ketoisovalerate with C. glutamicum has thus far not been reported.…”
mentioning
confidence: 99%
“…Recent studies also showed the successful employment of C. glutamicum for the production of the diamines putrescine and cadaverine (5)(6)(7)(8)(9)(10), the organic acids D-lactate, succinate, 2-ketoisovalerate, and pyruvate (11)(12)(13)(14)(15), the biofuels ethanol and isobutanol (16)(17)(18), xylitol (19), and heterologous proteins (20,21).…”
mentioning
confidence: 99%
“…From a metabolic viewpoint, diaminopentane is formed directly from lysine by decarboxylation, meaning that Corynebacterium glutamicum, which produces more than 1,000,000 metric tons of L-lysine per year, is a promising production organism. In a first proof of principle, a C. glutamicum wild type was modified by replacing homoserine dehydrogenase with heterologous lysine decarboxylase (cadA) from Escherichia coli (19,24). The yield of diaminopentane was, however, rather low, underlining that this modification can only be a first step toward a competitive industrial strain.…”
mentioning
confidence: 99%